Squamous cell carcinoma antigen: A potentially useful prognostic marker in squamous cell carcinoma of the anal canal and margin. Issue 13 (10th April 2013) - Williams, Matt; Swampillai, Angela; Osborne, Melanie; Mawdsley, Suzannah; Hughes, Rob; Harrison, Mark; Harvey, Richard; Glynne‐Jones, Rob; ,
Abstract : BACKGROUND: The objective of this retrospective study was to investigate the predictive value of pretreatment serum squamous cell carcinoma antigen (SCCAg) levels in 174 patients with squamous cell carcinoma of the anus who received concurrent chemoradiation between 1997 and 2010. METHODS: Pretreatment serum SCCAg measurements in patients with histologically diagnosed squamous cell carcinoma of the anal canal and margin who received chemoradiation were compared with clinical tumor classification and lymph node status for prognostic/predictive ability, including 1) tumor response after the completion of chemoradiation treatment, 2) disease recurrence, and 3) overall survival. Clinical measurements and scores were compared using Spearman rank tests, and survival was assessed in both univariate and multivariate survival analyses. RESULTS: The median pretreatment levels of SCCAg according to clinical tumor classification and clinical lymph node status were 0.8 μg/L in T1 tumors, 1.90 μg/L in T2 tumors, 2.5 μg/L in T3 tumors, 3.8 μg/L in T4 tumors, 1.35 μg/L in patients with N0 status, and 3.05 μg/L in patients with N0+ status (correlation coefficient: T‐classification, 0.43; lymph node status, 0.38; both P < .00001). Of the patients who had normal SCCAg levels, 95% achieved a complete response after initial treatment; and, of those who had elevated SCCAg levels, 86% achieved a complete response ( P = .05). Overall survival (hazard ratio, 2.5; P = .007) and disease‐free survival (hazard ratio, 2.2; P = .058) were worse for those who had elevated pretreatment serum SCCAg concentrations. CONCLUSIONS: Pretreatment SCCAg levels in patients with squamous cell carcinoma of the anal canal and margin were correlated with clinical tumor classification and clinical lymph node status. Elevated levels of SCCAg were associated with a reduced chance of achieving a complete response and an increased chance of recurrence and death. The authors recommend further studies to determine the prognostic value of SCCAg in anal squamous cell carcinoma and suggest the potential use of SCCAg as a stratification factor in future trials. Cancer 2013;119:2391‐2398 . © 2013 American Cancer Society . Abstract : The results from this retrospective analysis indicate that pretreatment squamous cell carcinoma antigen (SCCAg) levels in patients with squamous cell carcinoma of the anal canal and margin correlate with clinical tumor classification and lymph node status. In addition, elevated pretreatment levels of SCCAg are associated with a reduced chance of achieving a complete response and an increased chance of recurrence and death.